The development of the law relating to enforcement of arbitration agreements in the pathway of pro-arbitration policy / Arunachalam Kasi - Arunachalam, Kasi (2014)
Traditionally the courts of law have been the cove medium in enforcement and upholding of the rights and obligations provided by law.